2023
DOI: 10.3389/fmed.2023.1217156
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled therapies targeting prostacyclin pathway in pulmonary hypertension due to COPD: systematic review

Abdullah A. Alqarni,
Abdulelah M. Aldhahir,
Heba M. Bintalib
et al.

Abstract: BackgroundPulmonary hypertension due to chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD) is classified as group 3 pulmonary hypertension. Inhaled treprostinil, a prostaglandin I2 analogue also known as prostacyclin, has recently been approved as a first drug for patients with pulmonary hypertension secondary to ILD. However, due to a lack of evidence, no therapies are currently approved for those with COPD-associated pulmonary hypertension. Thus, this systematic review aims to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Inhaled treprostinil is the first approved therapy for patients with group 3 PH (only due to interstitial lung disease) as it improves exercise capacity ( 86 ). Our recent systematic review demonstrated that inhaled therapies targeting prostacyclin pathway can reduce pulmonary vascular resistance without worsening pulmonary gas exchange ( 87 ). Although the use inhaled nitric oxide is not currently approved for adults with all forma of PH, limited studies assessed the short-term efficacy of using inhaled nitric oxide in patents with PH due to COPD and demonstrated potential benefits in improving hemodynamic parameters in COPD ( 88 , 89 ).…”
Section: Imbalanced Vasoactive Gene Expression and Mediator Release I...mentioning
confidence: 99%
“…Inhaled treprostinil is the first approved therapy for patients with group 3 PH (only due to interstitial lung disease) as it improves exercise capacity ( 86 ). Our recent systematic review demonstrated that inhaled therapies targeting prostacyclin pathway can reduce pulmonary vascular resistance without worsening pulmonary gas exchange ( 87 ). Although the use inhaled nitric oxide is not currently approved for adults with all forma of PH, limited studies assessed the short-term efficacy of using inhaled nitric oxide in patents with PH due to COPD and demonstrated potential benefits in improving hemodynamic parameters in COPD ( 88 , 89 ).…”
Section: Imbalanced Vasoactive Gene Expression and Mediator Release I...mentioning
confidence: 99%